Optimal fresh-air utilization strategy for constant temperature and humidity air-conditioning system based on isocost line. (15th January 2023) - Wang, Cuiling; Wang, Baolong; Cui, Mengdi; Wei, Falin
Abstract: The constant temperature and humidity air-conditioning systems extensively applied in buildings and spaces, such as clean rooms and manufacturing facilities, are considerably energy intensive. To provide thermal comfort, ensure working efficiency, or maintain positive pressures in a workshop, a large amount of fresh air must be supplied indoors. The reasonable use of fresh air can reduce the cost (such as energy, CO2 emission, or money cost) of the air-handling process. An optimal fresh-air utilization strategy was developed to minimize the cost of operation based on considerations of the different costs for different handling processes in all working conditions. Straightforward isocost lines were developed to determine the optimal fresh-air ratio. Using this method, the performances of heating, ventilation, and air-conditioning systems in a workshop were simulated and tested. Results demonstrate that the proposed optimal strategy exhibits superior performance in terms of cost savings. Compared with commonly used strategies, the optimal strategy can reduce the total annual primary energy consumption by 8.3%–9.7%; and the reduction can be as high as 35% in the transition seasons. When the optimal fresh-air utilization strategy is applied in the field, the primary energy consumption is reduced by 6.4%–9.8% on typical days. Highlights: An optimal fresh-air utilization strategy is proposed to realize cost savings. The isocost line is developed to determine the optimal fresh-air ratio quickly. The optimal strategy is suitable for all weather and load conditions. A primary energy saving of 9.8% was realized in a practical project.